The impact of investor attention on green bond returns: How do market uncertainties and investment performances of clean energy and oil and gas markets affect the connectedness between investor attention and green bond? - Uckun-Ozkan, Aysegul (Asian Journal of Economic Modelling, 2024)
This paper empirically investigates the spillover between investor attention and green bond returns by utilizing the connectedness approach. We will examine the impact of uncertainty in the stock, bond, and energy markets, as well as the success of clean energy, oil, and gas investments, on the relationship between green bonds and investor attention. We find that there are positive but small spillovers between investor attention and green bond returns. Besides, the connectedness between investor attention and green bond market performance is stronger in the short run than in the long run. Further, there is a time-varying feedback effect between green bond returns and investor attention. The connectedness approach also implies that the effect of investor attention on green bond returns is greatest in the COVID-19 period. This impact decreased throughout the war era. It is crucial to analyze the behaviour of green bonds in both typical and exceptional market situations. Making a general assessment may lead to insufficient information about how green bonds behave in extreme market conditions. Additionally, in instances of highly volatile market conditions, investor attention can serve as a valuable instrument for predicting the green bond market performance.